Autism: The Movement Perspective - Anne M Donnellan (Frontiers Research Topics, 2015)
Autism Spectrum Disorders (ASD) is portrayed as cognitive and social disorders. Undoubtedly, impairments in communication and restricted-repetitive behaviors that now define the disorders have a profound impact on social interactions. But can we go beyond the descriptive, observational nature of this definition and objectively measure that amalgamate of motions and sensations that we call behavior?In this Research Topic we bring movement and its sensation to the forefront of autism research, diagnosis, and treatment. We gather researchers across disciplines with the unifying goal of recognizing movement and sensory disturbances as core symptoms of the disorder. We also hear confirmation from the perspective of autism self-advocates and parents. Those important sources of evidence along with the research presented in this topic demonstrate without a doubt that profound movement and sensory differences do exist in ASD and that they are quantifiable.The work presented in this Research Topic shows us that quantifiable differences in movements have a better chance than current observational techniques to help us uncover subtle solutions that the nervous system with autism has already spontaneously self-discovered and utilized in daily living. Where the naked eye would miss the unique subtleties that help each individual cope, instrumentation and fine kinematic analyses of motions help us uncover inherent capacities and predispositions of the person with autism. The work presented in this topic helps us better articulate through the voices of parents and self-advocates those sensory motor differences that current inventories could not possibly uncover. These differences are seldom perceived as they take place at timescales and frequencies that fall largely beneath our conscious awareness. To the person in the spectrum living with this disorder and to the caregiver creating accommodations to help the affected loved one, these subtleties are very familiar though. Indeed they are often used in clever ways to facilitate daily routines. We have waited much too long in science to listen to the very people that we are trying to define, understand and help.Being autism a social problem by definition, it is remarkable that not a single diagnosis inventory measures the dyadic social interaction that takes place between the examiner and the examinees. Indeed we have conceived the autistic person within a social context where we are incapable - by definition - of accepting those differences. The burden is rather placed on the affected person to whom much too often we refer to in the third person as "non-verbal, without intentionality, without empathy or emotions, without a theory of mind", among other purely psychological guesses. It is then too easy and shockingly allowed to "reshape" that person, to mold that person to better conform to our social expectations and to extinguish "behaviors" that are socially unacceptable, even through the use of aversive punishing reinforcement techniques if need be. And yet none of those techniques have had a single shred of objective scientific evidence of their effectiveness. We have not objectively measured once, nor have we physiologically characterized once any of those perceived features that we so often use to observationally define what we may think the autistic phenotype may be. We have not properly quantified, beyond paper-and-pencil methods, the effectiveness of interventions in autism.